Does environmental administrative penalty promote the quantity and quality of green technology innovation in China? Analysis based on the peer effect - Chen, Xuan; Zhan, Meng (Frontiers in Environmental Science, 2022)
Taking listed firms of heavily polluting industries in China's Shanghai and Shenzhen A-share from 2016 to 2020 as the sample, this paper analyzes the impact of environmental administrative penalty on the quantity and quality of corporate green technology innovation based on the perspective of peer enterprises. The results indicate that: (1) Environmental administrative penalty significantly promotes the quantity and quality of peer enterprises’ green technology innovation. (2) Heterogeneity analysis shows that the diversity of penalty, the competitiveness of the penalized enterprises, and the nature of the property rights of peer enterprises all contribute to the different impact of environmental administrative penalty on the peer enterprises’ green technology innovation. (3) Further analysis shows that when peer enterprises face high financing constraints, the promotion effect of environmental administrative penalty on the quantity and quality of their green technology innovation will be weakened. The research results expand the related research on direct government regulation and enterprise green technology innovation from the perspective of peer effect, and provides policy reference for the government to formulate differentiated environmental administrative penalty policies according to the heterogeneity of enterprise.